Enantioselective Ecotoxicity of Venlafaxine in Aquatic Organisms: Daphnia and Zebrafish. (6th June 2022) - Ribeiro, Ondina; Félix, Luís; Ribeiro, Cláudia; Castro, Bruno; Tiritan, Maria Elizabeth; Monteiro, Sandra Mariza; Carrola, João Soares
Abstract: Venlafaxine is a chiral antidepressant detected in aquatic compartments. It was recently included in the 3rd Watch List from the European Union. The present study aimed to investigate venlafaxine toxicity effects, targeting possible enantioselective effects, using two aquatic organisms, daphnia ( Daphnia magna ) and zebrafish ( Danio rerio ). Specimens were exposed to both racemate, ( R, S )‐venlafaxine (VEN), and to pure enantiomers. Acute assays with daphnia showed that up to 50 000 μg/L of the (R, S)‐VEN induced no toxicity. Organisms were also exposed to sublethal concentrations (25–400 μg/L) of ( R, S )‐, ( R )‐ and ( S )‐VEN, for 21 days. No significant effects on mortality, age at first reproduction, and size of the first clutch were observed. However, a decrease in fecundity was observed for both enantiomers at the highest concentration. Regarding zebrafish, the effects of venlafaxine on mortality, embryo development, behavior, biochemistry, and melanin pigmentation were investigated after 96 h of exposure to the range of 0.3–3000 μg/L. ( R )‐VEN significantly increased the percentage of malformations in comparison with ( S )‐VEN. Behavior was also enantiomer dependent, with a decrease in the total distance moved and an increase in avoidance behavior observed in organisms exposed to ( R )‐VEN. Despite the biochemical variations, no changes in redox homeostasis were observed. ( R )‐VEN also led to an increase in zebrafish pigmentation. The different susceptibility to venlafaxine and enantioselective effects were observed in zebrafish. Our results suggest that at environmental levels ( R, S )‐VEN and pure enantiomers are not expected to induce harmful effects in both organisms, but ( R )‐VEN increased malformations in zebrafish larvae, even at reported environmental levels. These results highlight the importance of including enantioselective studies for an accurate risk assessment of chiral pollutants. Environ Toxicol Chem 2022;41:1851–1864. © 2022 SETAC Abstract : Venlafaxine (VEN) is a chiral antidepressant excreted by urine and/or leaked by inappropriate disposal and reach aquatic compartments. The present study investigated venlafaxine toxicity effects, targeting possible enantioselective effects, using daphnia ( Daphnia magna ) and zebrafish ( Danio rerio ) using several endpoints.